How bricoleurs go international: a European cross-country study considering the moderating role of governmental entrepreneurship support programs - Tobias Kollmann; Simon Hensellek; Philipp Benedikt Jung; Katharina de Cruppe (The Journal of Technology Transfer, 2022)
Research increasingly suggests that innovativeness and internationalization are two intertwined pathways to growth for entrepreneurial ventures. However, both ways can be resource intensive and thus challenging. Therefore, theory points to the emerging concept of entrepreneurial bricolage to explain how resourceful behavior helps entrepreneurial ventures thrive despite facing the challenges associated with growth. At the same time, recent studies increasingly emphasize the importance of institutional support for successful venture growth. Combining both streams, this study explores product/service innovativeness as a mediator in the relationship between bricolage and the degree of internationalization and further investigates the moderating role of governmental entrepreneurship support programs in this relationship. By drawing on a unique dataset of 681 European entrepreneurial ventures, we find that bricolage is an important means for entrepreneurial ventures that target foreign markets, as it fosters product/service innovativeness and thereby enhances a venture's degree of internationalization. Interestingly, governmental entrepreneurship support programs do not affect the link between bricolage and innovativeness, but they influence how innovativeness translates into greater degrees of internationalization. We discuss the theoretical and practical implications of our findings.
Keywords: 600; Bricolage; Innovativeness; Internationalization; Governmental programs; Entrepreneurship; Context